Pelatihan Guru Pesantren Sultan Hasanuddin Gowa untuk membangun mitra pengembangan bahasa Indonesia bagi penutur asing - Ramly Ramly; Juanda Juanda; Azis Azis (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The role of Islmic Boarding School teachers can be increased for Indonesian language learning especially for foreignspeakers. The language competency of some Islmic Boarding School teachers, namely Arabic, is very supportive of Indonesianfor foreign spekers learning, especially for foreigners whose daily language background is Arabic. There is no information toensure that the potential of Islamic Boarding School teachers can be utilized for Indonesian for foreign spekers learning so thatthe Community Partnership Program (PKM) is carried out. The purpose of this PKM is to develop the competence of teachers inIslamic boarding schools so that they can teach Indonesian to foreign speakers. Training for 20 Sultan Hasanuddin Gowa IslamicBoarding School teachers' training has been carried out using lecture, discussion, assignment and simulation methods. The resultsof the training show that teachers who participated in the training experienced a significant change in their attitudes, abilities, andcommitments after they took part in the training compared to before training. It was concluded that this training succeeded inachieving the targets set.